Musical hallucinations, secondary delusions, and lack of insight: results from a cohort study - Buijk, Milou A.; Lauw, René F.; Coebergh, Jan Adriaan F.; Bouachmir, Ouarda; Linszen, Mascha M. J.; Blom, Jan Dirk (Frontiers in Psychiatry, 2023)
Introduction Although musical hallucinations do not tend to be accompanied by delusions, occasionally patients persistently accuse others of being responsible for causing the music they perceive, sometimes with severe social consequences such as frequently calling the police or moving house. In this study we seek to broaden our understanding of this rare type of musical hallucination that comes with secondary delusions and lack of insight, and to explore associations, underlying mechanisms, and treatment possibilities. Methods The present study is part of a cohort study on musical hallucinations carried out in the Netherlands from 2010 through 2023. Participants underwent testing with the aid of the MuHa Questionnaire, Launay-Slade Hallucinations Scale (LSHS), Schizotypal Personality Questionnaire (SPQ), Hamilton Depression Rating Scale (HDRS), and Mini Mental State Examination (MMSE). Additionally, they underwent a brain MRI, electroencephalogram, and audiological testing. Results Five patients out of a group of N = 81 (6%) lacked insight and presented with secondary delusions regarding the perceived music. They were all female, of advanced age, and hearing-impaired, and were diagnosed with cognitive impairment. In three patients (60%), risperidone was started. This had a positive effect on the hallucinations and secondary delusions. Conclusion The pathophysiological process underlying musical hallucinations is multifactorial in nature. We consider cognitive impairment the most likely contributing factor of the secondary delusions and lack of insight encountered in our patients, and antipsychotics the most beneficial treatment. On the basis of these small numbers, no definite conclusions can be drawn, so further research is needed to elucidate the underlying mechanisms and to develop evidence-based treatment methods for people experiencing this rare and debilitating combination of symptoms. Since the black box warning of risperidone cautions against the use of this drug in elderly persons with dementia, a proper comparison with the efficacy and safety of other antipsychotics for this group is paramount.